2019
DOI: 10.1177/1756286419836571
|View full text |Cite
|
Sign up to set email alerts
|

Risks and risk management in modern multiple sclerosis immunotherapeutic treatment

Abstract: In recent years, there has been a paradigm shift in the treatment of multiple sclerosis (MS) owing to the approval of a number of new drugs with very distinct mechanisms of action. All approved disease-modifying drugs primarily work directly on the immune system. However, the identification of an ‘optimal choice’ for individual patients with regard to treatment efficacy, treatment adherence and side-effect profile has become increasingly complex including conceptual as well as practical considerations. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 175 publications
(206 reference statements)
0
62
0
8
Order By: Relevance
“…The main difference between second line DMTs and immunosuppressant therapy is the selectivity of action. The latter are classical cytotoxic immunosuppressants that act by inhibiting DNA synthesis [38,39], while second line drugs act by suppressing or altering the immune system with more specific mechanisms [40].…”
Section: Plos Onementioning
confidence: 99%
“…The main difference between second line DMTs and immunosuppressant therapy is the selectivity of action. The latter are classical cytotoxic immunosuppressants that act by inhibiting DNA synthesis [38,39], while second line drugs act by suppressing or altering the immune system with more specific mechanisms [40].…”
Section: Plos Onementioning
confidence: 99%
“…In recent years, there has been a paradigm shift in the treatment of MS because of the approval of some new diseasemodifying drugs distinct mechanisms of action (Vaughn et al, 2018). However, the emergence of highly effective treatment options for MS has been accompanied by an increasingly complex array of adverse effects, especially with regard to immune compromise following long-term immune therapy (Klotz et al, 2019). It was reported that Fingolimod is also associated with an increased incidence of other skin malignancies (Velter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ðia me ty ri me nag ri në jo me ser gan èiø jø IS imu no mo duliuo jan èio gy dy mo var to ji mo draus min gu mà, ga li mas nedraus min go var to ji mo prie þas tis ir daþ ná, pa cien tø po þiû rá á vais tus, daþ niau sius in for ma ci jos apie li gà ir jos gy dy mà ðal ti nius. Dau ge lio kli ni ki niø ty ri mø duo me nys áro do, kad nuosek lus ir draus min gas LMV var to ji mas uþ tik ri na kli ni ki ná pre pa ra tø efek ty vu mà: su ma þi na pa û më ji mø skai èiø, il gina re mi si jos lai ko tar pius, lë ti na ne ga lios pro gre sa vi mà bei nau jø ir (ar) ak ty viø þi di niø for ma vi mà si MRT [6,7,14]. Ne ma þai ty ri mø pa ro dë, kad ne draus min gas LMV var to jimas yra sie ja mas su daþ nes niais li gos pa û më ji mais ir daþnes në mis hos pi ta li za ci jo mis bei ið ðiø veiks niø ky lan èiomis pa sek më mis -grei tes niu li gos pro gre sa vi mu ir pa di dëju sio mis gy dy mo sà nau do mis [15][16][17]19].…”
Section: Aptarimasunclassified
“…jan èius pre pa ra tus, ku rie pa ge ri no li gos val dy mà il ga lai këje per spek ty vo je [7]. Su ma þin da mi pa û më ji mø skai èiø, lëtin da mi ne ga lios pro gre sa vi mà bei nau jø ir ak ty viø þi di niø at si ra di mà gal vos sme ge nø mag ne ti nio re zo nan so to mogra fi jo je (MRT), imu no mo du liuo jan tys pre pa ra tai itin page ri no ser gan èiø jø gy ve ni mo ko ky bae [8].…”
unclassified
See 1 more Smart Citation